Bovine sperm HSP-70 molecules: a potential cryo-tolerance marker associated with semen quality and fertility rate - Pardede, Berlin Pandapotan; Kusumawati, Asmarani; Pangestu, Mulyoto; Purwantara, Bambang (Frontiers in Veterinary Science, 2023)
Introduction Freezability is the ability of sperm to maintain its vitality and quality from various stress during the cryopreservation process, which is very important for the success of fertilization in AI programs. Heat shock proteins (HSPs) are unique proteins induced in response to various stress, including excess reactive oxygen species (ROS) and oxidative damage to intracellular enzymes that can harm cells. This study aimed to analyze the potential of HSP-70 molecules in bovine sperm as a marker of freezability or cryo-tolerance, as well as its association with semen quality and fertility rate. Methods The classification of bulls is based on freezability (good freezability/GF and poor freezability/PF), which is obtained from the value of post-thaw viability using the SYBR-14/PI-flow cytometry. Semen quality assessed included sperm motility and kinetics (computer-assisted sperm analyses), plasma membrane integrity (HOS test), acrosome integrity (FITC-PNA), mitochondrial membrane (JC-1), and DNA damage (Halomax kit). The bull fertility rate assessment was analyzed based on the first service conception rate of each bull derived from data on the success of artificial insemination contained in the Indonesian-integrated National Animal Health Information System (iSIKHNAS). Gene expression levels of HSP-70 bovine sperm were performed using the RT-qPCR method. The protein abundance of HSP-70 bovine sperm was determined using the enzyme immunoassay (EIA) method. Results Bovine sperm HSP-70 molecules, at the gene and protein level, showed a higher abundance in GF (p < 0.05) than in PF bulls. The percentage of each parameter of frozen–thawed sperm quality was significantly higher in GF (p < 0.05) than in PF bulls. The HSP-70 molecules at the gene and protein levels were significantly positively correlated (p < 0.01) with the fertility rate. Furthermore, HSP-70 molecules were negatively associated (p < 0.01) with low mitochondrial membrane potential and sperm DNA damage and positively correlated (p < 0.01) with other frozen–thawed sperm quality parameters. The overall quality of frozen–thawed sperm was closely related (p < 0.01) to the fertility rate. Conclusion We may conclude that HSP-70 molecules in bovine sperm at the gene and protein level have the potential to be developed as a marker for cryo-tolerance or freezability, which may be utilized as a predictor of fertility and frozen–thawed sperm quality in bulls.